Analisis Pengaruh Indeks Pembangunan Manusia Dan Tenaga Kerja Terhadap Kemiskinan Di Provinsi Sumatera Utara - Dessy Chayani Elisabeth Sitanggang (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara Medan, 2020)
Poverty continues to be a major global problem, particularly in North Sumatra Province. The research aims to test and analyze the Effect of the Human Development and Labor Index on Poverty in North Sumatra Province. This type of data uses secondary data obtained from BPS Indonesia and also journals as research support. The analysis used in this study is a quantitative method and uses eviews10. In this model the independent variable used is the Human Development Index and Labor. While the dependent variable is poverty. Regression results show the Correlation Coefficient (R) obtained by multiple correlations of R = 0.53 or by 53%, it can be concluded that there is a strong correlation between the HDI variables and the Workforce on Poverty in North Sumatra Province. The coefficient of determination (R2) from the calculation of the coefficient of determination (R2) of 0.06 or 6% means that 6% of poverty in North Sumatra Province is influenced by HDI and labor. While 94% is influenced by other variables not examined.